The Relationship between Dickkopf-Related Protein-1 (DKK-1) Plasma Levels and Impaired Cognitive Function in HIV Patients - Yulia Trisna; Yuliarni Syafrita; Restu Susanti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Dickkopf-related protein – 1 (DKK-1) is an antagonist protein to the Wingless (Wnt)-β catenin signal. Dysregulation of Wnt-β catenin signaling by DKK-1 causes disruption of neuronal synapses, which can result in impaired cognitive function. Impaired cognitive function in people with HIV or HIV-associated neurocognitive disorder (HAND) is a spectrum of cognitive disorders related to HIV neuroinvasion and neuroinflammation, which significantly results in impaired cognitive function and daily activity. This study aimed to assess the relationship between plasma DKK-1 levels and impaired cognitive function in HIV patients. Methods: This study used a cross-sectional design, consisting of 84 HIV sufferers who went to the voluntary counseling and testing (VCT) polyclinic at Dr. M. Djamil General Hospital, Padang, Indonesia, in the period December 2022 - March 2023, who met the inclusion and exclusion criteria. Cognitive function was assessed using the Montreal Cognitive Assessment Indonesian version (MoCa-Ina), and daily activity function using the instrumental activity of daily living (IADL) examination. Plasma DKK-1 levels were measured using the enzyme-linked immunosorbent assay (ELISA) method. Results: The mean plasma DKK-1 level of HIV sufferers was 358.4 (+ 157.6) pg/mL. ANI type disorder was found in 78.6%, MND in 21.4%, and no HAD type. There was a significant relationship between plasma DKK-1 levels and impaired cognitive function in HIV patients (OR = 2.82, CI95% = 1.128-7.043, p = 0.025), but there was no significant difference in plasma DKK-1 levels between types of cognitive impairment ANI and MND (p = 0.858). Conclusion: Plasma DKK-1 levels are significantly associated with impaired cognitive function in HIV patients.